MMSC-LIKE LIMBAL CELLS COTRANSPLANTATION PROMOTES LOCAL IMMUNOCORRECTION AND CORNEAL GRAFT TRANSPARENT RETENTION IN HIGH RISK KERATOPLASTY - S. A. Borzenok; N. A. Onishchenko; Kh. D. Tonaeva; Y. A. Komakh; Y. V. Kovshun; N. A. Strusova (Вестник трансплантологии и искусственных органов, 2014)
Aim was to evaluate clinical results of donor corneal graft survival in high-risk recipients in co-transplantation of preserved allogenic limbal grafts. Materials and methods. Two types of penetrative keratoplasties were carried out in patients with corneal graft opacities and high risk of rejection (n = 69). Co-transplantation of donor cornea and allogenic MMSC-like limbal cells in the form of limbal transplants was carried out in the 1st group (n = 36); in the 2nd group (n = 33) only the cornea was transplanted. Results. Observation of the patients during one year after surgery showed that the rate of transparent cornea engraftment increased in the 1st group (86,1 against 69,7% in the 2nd group). The density of endothelial cells was also higher in the 1st group (85,9 against 76,2% in the 2nd group). At the same time, progressive decreasing of pro-inflammatory cytokines (IL-6, IFNγ, TNFα) and increasing of anti-inflammatory cytokines (IL-10, IL-1RA, TGFβ) along with higher level of HLA-G5 were revealed in the recipients’ tear fluid in the 1st group in comparison to the 2nd group. Conclusion. Simultaneous transplantation of preserved limbal grafts with corneal graft in high-risk keratoplasty favors the transparent cornea engraftment, obviously, this is due to immunoregulatory activity of the MMSC-like limbal cells.